EFEKTIFITAS PELAKSANAAN PROGRAM TNI MANUNGGAL MEMBANGUN DESA ( TMMD) DALAM MEWUJUDKAN KETAHANAN WILAYAH - Purwatiningsih, Eny (Jurnal Ketahanan Nasional, 2013)
This paper explained the TNI program conduct in villageâs building. The qualitative data showed TMMDâs target consisted of physical and additional target and also the non-physical target had been achieved. The TMMD Program conductâs effectiveness had positive effect on regional resilience. It showed that TMMD Program able to enhanced the unity and unifi cation in the community and able to grew the decreasing togetherness. Therefore the program would be able to strengthened and enhanced the integrated of the TNI and people which would be enhance the peopleâs wealth, and also strengthened the unifi cation of the TNI and people to supported nationalâs defense.Keywords: TNI, TMMD, Villageâs Building, and Regional Resilience.